2022
DOI: 10.1590/fst.116621
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of lycopene from tomato pomace and its protective effects on renal injury in diabetic rats

Abstract: The aim of this study was to investigate the protective effects of lycopene from tomato pomace on renal injury in diabetic rats. Lycopene was extracted from tomato pomace. The rats were divided into control, model and 10, 20 and mg/kg lycopene groups. The diabetic nephropathy model was constructed in the latter four groups. Then, the latter three groups were treated with 10, 20 and mg/kg lycopene, respectively. After four weeks of treatment, compared with the model group, in 20 and 40 mg/kg lycopene groups the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Besides, edible coatings are transparent films that can also be used in fruit packaging as an alternative to the wax that naturally occurs on the surface of the fruit. 90…”
Section: Starch-based Hydrogelsmentioning
confidence: 99%
“…Besides, edible coatings are transparent films that can also be used in fruit packaging as an alternative to the wax that naturally occurs on the surface of the fruit. 90…”
Section: Starch-based Hydrogelsmentioning
confidence: 99%
“…Indeed, there was an association between free radical-induced lipid peroxidation and decreased antioxidant enzymes activity, linked to elevated oxidative stress in DM, a key factor for diabetic complications. Also, alteration in the endogenous free radicals quenching defense mechanisms may cause insufficient scavenging, leading to oxidative damage and tissue injury (Xie et al, 2022). Additionally, Eliza et al (2009) showed that STZ elevate the lipid peroxides level and reduce the antioxidant enzymes activity of diabetic rats.…”
Section: Effect Of Tomato Juice On Antioxidant Statusmentioning
confidence: 99%
“…On the other hand, having healthy diets as shown with many previous evidences; eating fruits and vegetables lowers the risk of oxidative damage due to their great levels of the natural antioxidants (Ojetola et al, 2021). So it is quite important to consume healthy diets and/ or consume dietary food supplements containing antioxidant molecules in order to regulate oxidative stress (Xie et al, 2022) and help to maintain cell and tissue homeostasis in addition to prevent inflammation and chronic metabolic diseases (Dini, 2021). Again, the potential main role for the antioxidants within the human body is the defense from free radicals; stopping and/ or decreasing free radicals development by different enzyme activities (Xie et al, 2022) such as glutathione peroxidase (GSH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations